Tracking Control Performances Of A Dual-Limb Robotic Arm System - Md Ghazaly, Mariam; Tee, Siau Ping; Tan, Ping Khai; Chong, Shin Horng; Che Amran, Aliza; Jamaluddin, Muhammad Herman; Mohd Aras, Mohd Shahrieel (IJENS Publishers, 2016)
This paper discuss the tracking control performances of a dual-limb robotic arm system for precision motion and high speed response. In this paper, the focus is to fabricate & analyze the control performances of an upper duallimb robotic arm system which are able to move in parallel motion. The experimental results are obtained through open-loop and closed-loop test. The system transfer function is evaluated experimentally via system identification method. In this paper the Proportional and Derivative (PD) controller is used to control the trajectory motion of the dual-limb robotic arm system. The PD controller with proportional gain Kp = 169 and derivative gain KD = 1.1412 shows good performances using step input reference. To further verify the robustness of the controller, tracking control experiments are performed with rectangular & triangular input trajectory. The PD controller shows the dual-limb robotic arm system able to show good performances with the steady state error less than 0.4° for the 15° triangular input references with 0.1Hz frequency, respectively.